Reverse emulsion polymerization : study of variables’ effects on nanogel synthesis and behaviour - Ho, Cheng En (2019)
Stable water-dispersible nanohydrogels of crosslinked acrylic acid-co-acrylamide (Poly AAc-co-AM) polymer were formed by inverse emulsion polymerization using N,N'methylenebisacrylamide (NNMBA) as cross-linking agent, and polyoxyethylene sorbitan mono-oleate (TWEEN80) and sorbitan monooleate (SPAN80) as cosurfactants. Various factors (temperature, initiator type, solvent ratio and surfactant ratio) that affect the reaction were arranged in a matrix and experiments were carried out in order to test how the factors affect the formation of the nanogel. After which, the results were arranged to identify possible correlations between factors. Based on the results, it was observed that nanogel formed using ammonium persulfate (APS) as initiator have a smaller unswollenparticle size ranging from 14-60 d.nm than when the initiator 2,2'-Azobis(2-amidinopropane) dihydrochloride (AAPH) was used, whereas swollen sizes were comparable between the two; this led to higher swelling ratios for APS nanogel. Nanogel formed using AAPH as initiator were observed to have a more stable range of sizes of between 52-66 d.nm.